PENGARUH PENGEMBANGAN SUMBERDAYA MANUSIA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA INSPEKTORAT KABUPATEN MOROWALI - Nugraha, Rizky (Katalogis, 2016)
The aims of this research are: 1) to determine and analyze the influence of human resource development, work discipline, and work environment on the performance of employees in the Inspectorate Office of Morowali Regency; 2) to determine and analyze the influence of human resource development on the employees’ performance; 3) to determine and analyze the influence of work discipline on the employees’ performance; 4) to determine and analyze the influence of work environment on the employees’ performance; 5) to determine and analyze the influence of human resource development, work discipline, and work environment on the performance of civil servants and contractual employees. The type of the research is survey and causal and it involves 42 subjects who are selected through census method. Based on the test of multiple linear regressions, it is shown that: 1) human resource development, work discipline, and work environment simultaneously have positive and significant influence on the performance of employees in the Inspectorate Office of Morowali Regency; 2) human resource development has positive and significant influence on employees’ performance; 3) work discipline has positive and significant influence on employees’ performance; 4) work environment has positive and significant influence on employees’ performance; 5) there is a difference of human resource development between civil servants and the contractual employees; and there is no difference of work discipline and work environment between civil servants and the contractual employees.